A Political Economy Analysis of Public Spending Distribution for Disaster Risk Reduction in Bangladesh - Islam, Shafiqul; Chu, Cordia; Smart, James C. R. (European Journal of Sustainable Development, 2019)
Bangladesh is one of the resource-scarce countries most vulnerable to climate-related disasters, particularly flood and cyclone. Based on the semi-structured in-depth interviews of 38 stakeholders and literature review, this study examined the public spending distribution process in DRR. This paper demonstrates how the processes of political economy- enclosure, exclusion, encroachment, and entrenchment occurs in the Disaster Risk Reduction (DRR) efforts of Department of Disaster Management (DDM), particularly the distribution of flood shelters. Enclosure occurs when DRR projects are allocated to less vulnerable areas or broaden the influence of dominant actors into the public spending. Exclusion happens when DRR efforts reduce vulnerable people?s access to public funds or marginalize disadvantaged stakeholder in decision-making process. Encroachment occurs when the distribution of DRR projects and selection of location and issues increase the environmental hazards or lead to other forms of disaster risk. Entrenchment happens when DRR projects aggravate the injustice or increase the grabbing of resources by the elites and increase inequality a community. This research explored that exclusionary forms of fund distribution of DRR happen locally and nationally. DRR related distribution have encroached through DRR project distribution without discussing local needs. Most severely, DRR related unequal distribution have entrenched social class making the backward communities vulnerable to climate-related disasters. Influencing practitioners of DRR need to take necessary actions to eliminate the potential risks from the processes of enclosure, exclusion, encroachment, and entrenchment happens in DRR related project fund allocations. Keywords: Bangladesh, Disaster Risk Reduction, Fund Distribution, Political Economy